Marine Sponges in a Snowstorm – Extreme Sensitivity of a Sponge Holobiont to Marine Oil Snow and Chemically Dispersed Oil Pollution - Vad, Johanne; Duran Suja, Laura; Summers, Stephen; Henry, Theodore B.; Roberts, J. Murray (Frontiers in Microbiology, 2022)
Holobionts formed by a host organism and associated symbionts are key biological units in marine ecosystems where they are responsible for fundamental ecosystem services. Therefore, understanding anthropogenic impacts on holobionts is essential. Sponges (Phylum Porifera) are ideal holobiont models. They host a complex microbial community and provide ecosystem services including nutrient cycling. At bathyal depths sponges can accumulate forming dense sponge ground habitats supporting biodiverse associated communities. However, the impacts of spilled oil and dispersants on sponge grounds cannot be understood without considering exposures mediated through sponge filtration of marine snow particles. To examine this, we exposed the model sponge Halichondria panicea to oil, dispersant and ‘marine oil snow’ contaminated seawater and elucidate the complex molecular response of the holobiont through metatranscriptomics. While the host response included detoxification and immune response pathways, the bacterial symbiotic response differed and was at least partially the result of a change in the host environment rather than a direct response to hydrocarbon exposure. As the sponge host reduced its pumping activity and internal tissue oxygen levels declined, the symbionts changed their metabolism from aerobic to anaerobic pathways possibly via quorum sensing. Furthermore, we found evidence of hydrocarbon degradation by sponge symbionts, but sponge mortality (even when exposed to low concentrations of hydrocarbons) implied this may not provide the holobiont with sufficient resilience against contaminants. Given the continued proposed expansion of hydrocarbon production into deep continental shelf and slope settings where sponge grounds form significant habitats it is important that dispersant use is minimised and that environmental impact assessments carefully consider the vulnerability of sponge holobionts.